Characteristics of CPO Extraction Results from Spinner Machine Test Capacity 15-45 Kg for Home Industrial Scale - Yazid Ismi Intara; Reza Jarot Widianto; Bosman Sidebang Sidebang (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This research aims to obtain the characteristics of CPO extraction results using a home industry spinner machine and determine the capacity of palm fruit suitable for CPO extraction using the spinner machine. Methodology: The spinner machine tested used a speed of 1800 rpm for 15 minutes, with capacity ratios of 15, 30, and 45 kg. The spinning process produces oil that will come out through the oil drain hole. Testing these three capacities will determine which one is more capable of producing CPO oil and is safe for engine rotation. Observing the characteristics of CPO involved yield tests, free fatty acid (FFA) tests, impurity content tests, and water content tests. Results: The yield test results ranged from 19.66% to 21.6%, the FFA test results ranged from 4.096% to 5.376%, the water content test results ranged from 0.2% to 0.6%, and the dirt content test results ranged from 2% to 5%. Findings: The 30 kg capacity was the most effective and efficient for CPO extraction using the home industry spinner machine. Novelty: The use of spinner machines in the home industry for CPO extraction has not been widely studied, and this research identifies the optimal capacity and efficiency of the spinner machine. Originality: This study provides new insights into the application of spinner machines for CPO extraction, highlighting their potential use in the home industry. Conclusions: The 30 kg capacity was the most effective and efficient for CPO extraction using the home industry spinner machine. Paper Type: Experimental Research Article Keywords: CPO, Extraction, home industry, spinner